Contracting Institutions, Property Rights and Economic Growth in the Post-90s Albania - Mario Curcija (European Scientific Journal, ESJ, 2018)
Economists often emphasize the role of institutions in order to explain the difference in wealth and development among different countries and in their researches they mark correlation between institution and economic development. This paper tests the validity of these models referring to Albania using time-series data from 1993 to 2015. There is evidence of significant positive effect of property rights on economic growth and credit to private sector, while there is evidenced insignificant impact of contracting institutions on economic outputs. A plausible explanation of these differences may be the different flexibility towards changes on property right institution rather than contracting institutions.